2007
DOI: 10.1016/j.jtcvs.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the left ventricular outflow tract in fixed subaortic stenosis and intact ventricular septum: An echocardiographic study in children and adults

Abstract: Hearts with isolated subaortic stenosis have abnormal left ventricular outflow tract geometry that postoperatively showed changes in left ventricular outflow tract width and aortoseptal angle. Compared with controls, the aortoseptal angle does not "normalize" when surgery is performed in older patients, suggesting that left ventricular outflow tract geometry may be remodeled in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…12 Furthermore, the LVOT obstruction eventually leads to concentric left ventricular hypertrophy and remodeling over time, which could conceivably also contribute to the development of AR. 13,14 Barkhordarian et al 15 reported that in patients under 10 years of age with an isolated subaortic membrane, the AoSA did change after surgical removal of the membrane, suggesting that the LVOT geometry may be remodeled in younger patients. This might explain why steeper AoSA were not associated with subaortic membrane recurrence in an eight-year follow-up study by Geva et al 16 Furthermore, an interaction between hemodynamic and genetic stimuli may determine the fate of patients with abnormal AoSA.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, the LVOT obstruction eventually leads to concentric left ventricular hypertrophy and remodeling over time, which could conceivably also contribute to the development of AR. 13,14 Barkhordarian et al 15 reported that in patients under 10 years of age with an isolated subaortic membrane, the AoSA did change after surgical removal of the membrane, suggesting that the LVOT geometry may be remodeled in younger patients. This might explain why steeper AoSA were not associated with subaortic membrane recurrence in an eight-year follow-up study by Geva et al 16 Furthermore, an interaction between hemodynamic and genetic stimuli may determine the fate of patients with abnormal AoSA.…”
Section: Discussionmentioning
confidence: 99%
“…The right ventricular outflow is preserved without a septal incision and without the moiety that is required for the "apron extension" shown in Figure 30 accounts for 15-20% of all cases of LVOTO [133]. The most common form of subvalvar stenosis is a fixed obstruction due to abnormally present fibromuscular structures in the LVOT.…”
Section: Ross and Ross-konno Proceduresmentioning
confidence: 99%
“…Stress level increases were consistent with cellular flow studies showing growth factor stimulation and cellular proliferation. Echocardiographic studies in patients with fixed subaortic stenosis and intact ventricular septum suggest that, in addition to a steepened aortoseptal angle, these patients also have a significantly wider mitral-aortic separation, a marked aortic valve dextroposition, an increased left ventricular wall thickness, an increased septal thickness, and a smaller LVOT width [133]. A steepsteepened aortoseptal angle in patients up to 10 years of age [133].…”
Section: Pathophysiologymentioning
confidence: 99%
“…1 In reality, subaortic membrane is not congenital but an acquired lesion that forms due to steep angel between left ventricle and aorta. 2 Turbulence of blood flow at this angel results in endocardial injury that initiates fibrosis and ultimately membrane formation.…”
Section: Introductionmentioning
confidence: 99%